Comfort and energy performance analysis of different glazing systems coupled with three shading control strategies. (28th May 2018) - Atzeri, Anna Maria; Gasparella, Andrea; Cappelletti, Francesca; Tzempelikos, Athanasios
Abstract : Shading control strategies are often required to optimize the balance between solar gains, daylight availability, glare protection, and view to the outside. Automated shading operation, when properly designed, may avoid performance losses due to manual operation while maintaining indoor environmental comfort. In this work, the integrated performance of different glazing systems coupled with three control approaches for roller shades is presented for a typical office space. The first control is a standard open–closed operation based on a workplane illuminance range, while the other two are able to set intermediate shade positions according to the solar position to maximize daylighting. The third control addresses excessive daylight on the workplane by imposing a workplane illuminance threshold to reduce the risk of daylight discomfort glare. Daysim, based on Radiance and the daylight coefficient method, was used to calculate the annual illuminance profile over the workplane, and Evalglare was used to calculate glare indexes. EnergyPlus was used for thermal comfort and energy analysis. The results were processed through a MATLAB code for transferring required information from one tool to another. Moreover, to assess the global performance of the shading controls and fenestration configurations studied, visual and thermal comfort were evaluated through a set of metrics able to express both the availability (the fraction of time with acceptable comfort conditions at specific positions) and the spatial usability (the fraction of space simultaneously within comfort range at specific moments). The energy performance was also quantified in terms of primary energy demand for heating, cooling, and lighting. The results showed that it is possible to balance daylighting, thermal and visual comfort, and energy use. This can be achieved by simultaneously selecting shading controls that allow adequate daylight without causing glare, and glazing properties with good thermal performance that allow adequate daylight (high visible transmittance) but limit solar gains (lower solar transmittance or solar heat gain coefficient [SHGC]) for moderate and cooling-dominated climates.